Pembentukan Keluarga Sakinah: Studi Kasus Alumni Santri Pengabdi di Pesantren Ziyadatut Taqwa Tlanakan Pamekasan - Zainul Syafaat, Muhammad; Shobirin, Muh.; Sulfa, Nafilah (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the process of forming sakinah families among alumni male santri who served at Ziyadatut Taqwa Islamic Boarding School, Tlanakan, Pamekasan, and to identify the impacts of this practice on their family life. This research employs a qualitative approach using a case study design. Data were collected through field observations, in-depth interviews with serving santri, kiai, and family members, as well as supporting documentation related to family development practices within the pesantren. Data analysis was conducted descriptively through data reduction, thematic categorization, and inductive conclusion drawing. The findings indicate that comprehensive spiritual and moral guidance provided by the kiai plays a significant role in shaping sakinah families, particularly through the cultivation of patience, humility, emotional maturity, and conflict management skills. Positive impacts include strengthened family spirituality, increased personal maturity, and harmonious household relationships. However, negative impacts were also identified, such as limited family time, role strain between service and family responsibilities, and potential emotional dependence on the kiai in household decision-making. Therefore, balancing pesantren service and family responsibilities is essential to achieving sustainable sakinah families.